SOLUSI PROBLEMATIKA PENYIDIKAN DALAM KERANGKA EFEKTIVITAS SISTEM PERADILAN PIDANA DAN REKOMENDASI PEMBENTUKAN LEMBAGA âPENYIDIKAN LANJUTANâ DALAM PEMBAHARUAN KUHAP - Gunakaya, A. Widiada (Sekolah Tinggi Hukum Bandung, 2011)
Criminal Justice System is a method of crime prevention by means of the Criminal Code. The way it works by actualizing, concretizing, functionalizing, and operationalizing the provisions of the Criminal Law in a criminal justice mechanism. The goal is to solve crimes as quick as possible by completing criminal matters into submission. To achieve its objectives, the components must work together in a systemic justice in all phases of criminal justice. But at the level of investigation as a prejudice stage, found problems with noncompliance with the formal and substantive requirements of an investigation. Consequently action of